Unravelling the complexity of Love and Deception in Vikas Sharma’s Novel ‘Love’s Not Time’s Fool’ (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Love is one of the human emotions, having different colours namely - affectionate love, conjugal love, sibling love, platonic love, spiritual love, erotic love and so on. Love is the most appealing emotion but it creates so many complexities to unravel, though its definition and positive achievements are not definite. Sometimes the deception in live may create drastic changes in the nature and life of someone like Tulsidas, Radha, Meera, Heer, Ranjha etc. Living in tension and lost in the maize of the world, everyone craves for true love to soothe and make the life meaningful and rudderless. The present paper will deal with Vikas Sharma’s Love’s Not Time’s Fool (2021) to showcase a bold, thought-provoking, and chaotic rhythm of love and deception through Richa, Abhilash, Malya, Robert Lee, Nikki and Ishqui etc. in the modern world of artificiality, unsustainability, dishonesty, selfishness, and opportunity